Разработка унифицированных программно-технических средств для реализации устройств противоаварийной автоматики в распределенных компьютерных системах - Крылова, Виктория Анатольевна; Мирошник, Анатолий Николаевич (Український державний університет залізничного транспорту, 2015)
Статья посвящена разработке и усовершенствованию унифицированных методов для построения программно-технического комплекса для реализации устройств противоаварийной автоматики в распределенных компьютерных системах. Предложено решение задач противоаварийной автоматики, стоящих как перед разработчиками и проектировщиками. Предложен перспективный подход к решению проблемы, заключающийся в постепенном отказе от собственного мелкосерийного производства комплектующих в пользу стандартных готовых решений, при доступности их на рынке.

The article is devoted to the development and improvement of standardized methods for building software and hardware complex for the implementation of emergency control devices in distributed computing systems. The solution of problems of emergency control, facing both developers and designers. Proposed approach to addressing the problem in phasing out their own small-scale production of standard components to complete solutions, with their availability in the market. It is shown that in the process of development and subsequent implementation of standardized software and hardware systems to meet the challenges of emergency control devices for developers and designers, a number of specific issues. From a developer's perspective, the main issues are the support to date the entire range of standard components used in the manufacture of the product, and implementation of various protocols of interaction with the external to the product input-output. One promising approach is the phasing out of their own small-scale production of standard components to complete solutions, with their availability in the market. From the perspective of the designer, the main objective is the integration of devices from various manufacturers in devices of emergency control of the designed object. In accordance with current trends, for solving this problem it requires first and foremost a systematic approach to the subject in terms of the distribution of functions between devices of emergency control devices, network design object, interface devices from different manufacturers with one another.
Development of software-technical unified funds for Implementation realization automation devices in distributed of computer systems
Keywords: унифицированные методы; программно-технические средства; компьютеризированные системы; распределенные системы; устройства противоаварийной автоматики; standardized methods; software and hardware; computerized systems; distributed systems; emergency control device